2016
DOI: 10.1371/journal.pone.0161342
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Tobacco Smoke on Protein and Metal Levels in the Serum of Women during Pregnancy

Abstract: BackgroundTobacco smoking by pregnant women has a negative effect on fetal development and increases pregnancy risk by changing the oxidative balance and microelements level. Smoking affects the concentration, structure and function of proteins, potentially leading to various negative effects on pregnancy outcomes.Methodology/Principal FindingsThe influence of tobacco smoke on key protein fractions in smoking and non-smoking healthy pregnant women was determined by capillary electrophoresis (CE). Concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…One possible explanation is the impact of pregnancy on zinc status. Decreased serum zinc is common in pregnancy with reported mean values of approximately 58-60 μg/dL at term [66-69]. During pregnancy, women with serum zinc values <56 μg/dL are considered zinc deficient [70] and the mean serum zinc value in the NBCS study participants was below this definition of zinc sufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is the impact of pregnancy on zinc status. Decreased serum zinc is common in pregnancy with reported mean values of approximately 58-60 μg/dL at term [66-69]. During pregnancy, women with serum zinc values <56 μg/dL are considered zinc deficient [70] and the mean serum zinc value in the NBCS study participants was below this definition of zinc sufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the level of total protein in smokers tends to be lower than non-smokers. Although the increasing level of oxidative stress due to cigarette-smoke exposure proved to stimulate more proteins production for rebalancing [26], higher oxidation of the albumin also rapidly cleared from the circulation and degraded [27]. In this study, total protein in the blood of cigarette smoke-rat groups and non-cigarette smoke groups showed nearly similar levels (Figure 2A).…”
Section: Resultsmentioning
confidence: 50%
“…In other populations, investigators have observed either the opposite relationship or no significant difference . One possible explanation for our observations would be a modulation of the effect of smoking by pregnancy, although the findings of other recent work are generally inconsistent with this idea . To simplify interpretation of the FS-SRM results, it was decided that statistical analyses should focus on variation that could not be formally explained by differences in protein concentration.…”
Section: Resultsmentioning
confidence: 85%
“…30 One possible explanation for our observations would be a modulation of the effect of smoking by pregnancy, although the findings of other recent work are generally inconsistent with this idea. 31 To simplify interpretation of the FS-SRM results, it was decided that statistical analyses should focus on variation that could not be formally explained by differences in protein concentration. Thus, an attempt was made to correct for these differences using simple normalization ( eq S1 ), for which the compositional analysis (see above) and the result in Figure 5 A provided some justification.…”
Section: Resultsmentioning
confidence: 99%